More cognitive gains from social activity in the oldest-old: evidence from a 10-year longitudinal study - Zhai, Boyu; Liu, Xiaomei; Fu, Jiangning; Zhu, Xinyi; Li, Juan (Frontiers in Psychology, 2024)
Background Previous research has indicated that engagement in social activities has proven advantageous for diminishing the likelihood of cognitive decline. However, no study has examined whether such cognitive benefits were to a similar extent for the young-old, the old–old, and the oldest-old groups. The purpose of this research was to determine whether aging would have an impact on the changes in cognitive function that would occur in older adults with varying degrees of social involvement. Methods The sample for this study comprised 4,481 older adults who participated in the Chinese Longitudinal Healthy Longevity Survey (CLHLS) during the waves spanning from 2008 to 2018. At baseline, participants were classified into the young-old (60–69 years; Mage = 66.66; SD = 1.87), the old–old (70–79 years; Mage = 74.21; SD = 2.82), and the oldest-old (80 years or older; Mage = 86.46; SD = 5.71) groups. Results The level of cognitive function decreased as participants aged. Importantly, compared to those lacking social activities, individuals who were got involved in social engagement at baseline had slower rates of cognitive decline over time. Furthermore, compared with the young-old group and the old–old group, the impact of social activity engagement on slowing cognitive decline was more salient for the oldest-old group. Conclusion Active engagement in social activities can slow age-related cognitive decline, particularly for the oldest-old group. To preserve cognitive function with aging, attention and resources should be allocated to encourage social activity engagement.